2000
DOI: 10.1093/jac/46.3.451
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazoles in the treatment of alveolar echinococcosis: a comparative study and review of the literature

Abstract: Mebendazole and albendazole are the drugs of choice for the treatment of alveolar echinococcosis. In this open-labelled observational study we present and evaluate the outcome of long-term treatment with these drugs and present results of different treatment regimens. Thirty-five patients were started on either mebendazole or albendazole at the beginning of 1992 and followed for an average of 39 months (range 12-79 months). Treatment was classed as successful if the disease had not progressed for>1 year and if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
106
2
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 19 publications
1
106
2
4
Order By: Relevance
“…Mebendazole has been extensively used to treat gastrointestinal parasitic infections in humans, and in this capacity, it has shown remarkable efficacy and safety (17,18). Furthermore, clinical data from long-term mebendazole therapy in the treatment of alveolar echinococcosis suggest that mebendazole should also exhibit minimal toxicity when used as a cancer therapy (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mebendazole has been extensively used to treat gastrointestinal parasitic infections in humans, and in this capacity, it has shown remarkable efficacy and safety (17,18). Furthermore, clinical data from long-term mebendazole therapy in the treatment of alveolar echinococcosis suggest that mebendazole should also exhibit minimal toxicity when used as a cancer therapy (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Mebendazole is more suited for clinical study than other benzimidazoles identified in our screen given its status as a marketed drug, its oral availability, and its favorable safety profile in long-term treatment regimens (19). In contrast, a pilot study of albendazole treatment in advanced cancer resulted in increased levels of neutropenia in treated subjects (22).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intake of benzimidazoles, however, may be complicated by serious side effects, and benzimidazoles are expensive drugs. 19 Recent case reports describe a parasitocidal effect for benzimidazoles, suggesting the possibility for definite discontinuation of the medication. 5,6,20 Thus, parameters indicating death of the parasite would allow the discrimination of a subgroup of patients in whom long-term medical treatment could be discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Eight patients with new signs of progression 18 months after discontinuation of benzimidazoles were restarted on continuous dosing of ABZ. 19 Shortly after starting ABZ, rising transaminases forced the change to MBZ in 1 case; the patient has been asymptomatic since. The other 7 patients tolerated the reinitiation of treatment well.…”
Section: Discussionmentioning
confidence: 99%
“…Such parasitostatic effect of albendazole on parasite germinating cell is also known in Echinococcus multilocularis. After cessation of albendazole treatment, the growth of larvocysts is resumed (Reuter et al, 2000). When a 10-day-administration of albendazole was completed during the first hospitalization, similar regeneration of Trichinella females parasitizing in intestine could have occurred and the production of new born larvae might continue.…”
Section: Discussionmentioning
confidence: 99%